Talk the talk and walk the walk: a novel training for medical students to promote decoloniality in global health - Ratner, Leah; Sridhar, Shela; Owusu, Sheila; Rosman, Samantha L.; Molina, Rose L.; Kasper, Jennifer (Frontiers in Education, 2024)
To date, the history of colonialism has permeated nearly every aspect of our conceptions, structures, and practices of global health; yet, there are no published medical school curricula aimed at promoting decoloniality in global health. We developed a pilot course for medical students to examine the history of colonialism, power, and positionality; promote self-reflection; and teach strategies for dismantling coloniality in global health. This five-part course was offered to students completing a scholarly project in global health with a mixed in-person/virtual format and online pre-session preparation materials. A pre-course survey on prior experiences in global health and self-efficacy was administered, and a reflection piece was analyzed for themes. After completion of the course, the students again completed the self-efficacy questionnaire, a course feedback survey and a semi-structured interview that was analyzed for themes. On average, the students felt that the course was relevant to their global health scholarly project and that the course met their learning objectives. There was a trend toward increased self-efficacy in decoloniality knowledge and skills following the course. In the post-course structured interviews, students raised issues reflected in the course materials including local project leadership; how identity, privilege and positionality influence relationships and the ability to attain mutual trust; project sustainability; and power dynamics. Undergraduate medical education in global health equity and decoloniality can play an important role in teaching future generations to dismantle the colonialism ingrained in global health and reimagine a global health practice based on equitable partnerships, community needs, and local leadership.